English and Nature: An Ecocritical Study Through English Narrative Text - Widyaiswara, Tiara; Luthfiyati, Dian; Nurman, Moh.; Nadhiah, Sirli (Universitas PGRI Madiun, 2024)
The urgency of this research is due to the problems being faced by Indonesia regarding the destruction of nature and the lack of human awareness of the relationship between humans and nature, which is an important factor behind the destruction of nature that is happening today. The author uses eco-ELT theory as an approach that integrates environmental issues into English language learning. The subject of this study is narrative text in the English textbook